Application of PGPR from sugarcane roots and mimosa roots on chili peppers (Capsicum frutescens L.) - Khoirul Bariyyah (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Chili pepper is a high-value horticultural crop that has significant nutritional and economic value. Plant growth-promoting rhizobacteria (PGPR) play a vital role in enhancing plant growth and productivity while supporting sustainable agriculture. This study evaluated the effect of PGPR derived from sugarcane roots and mimosa roots applied to chili pepper plants. The study was conducted using a factorial randomized complete block design. The first factor was the concentration of sugarcane root PGPR (0, 10, 20, 30 mL L-1), and the second factor was the mimosa root PGPR (0, 10, 20, 30 mL L-1). Observation variables included nitrogen uptake, plant height, flowering age, and fruit weight. The results showed that the application of sugarcane root PGPR had a significant effect on plant height and nitrogen uptake, with a concentration of 20 mL L-1 producing the highest nitrogen uptake (1.66 g). PGPR from mimosa root significantly affected flowering age and fruit weight, with a concentration of 30 mL L-1 significantly increasing fruit weight. However, the combination of both types of PGPR did not have a significant effect on all the variables observed. Thus, the application of PGPR from sugarcane root and mimosa root separately effectively increased the growth and yield of chili pepper plants, while the combination of both did not show a synergistic effect. Keywords: chili; Mimosa pudica; nitrogen